Influence of renewable energy sources on the scheduling on thermal power stations and its optimization for CO2 reduction. (10th October 2021) - Mathi, Ramalingam; Jayalalitha, Subbaiahan
Abstract: The thermal power of the total power demand accounts for the total of 60% in India, with the penetration of the nonconventional energy sources the grid management becomes a tedious job in maintaining the grid stability, and adding to the woes the environmental norms become stricter as it is a tough job to maintain to lesser CO2 emissions in the atmosphere. Hence this article aims with the integration of the grid management with the renewable energy sources and reduction of CO2 and also strives for the grid stability with the smart grid. And the thermal scheduling optimization is done with the novel bat algorithm.